Playing to Focus: A Systematic Review of Reveal-and-React Board and Card Games for Executive Function Development in Children - Charifa, Prisyafandiafif; Apriliani, Ima (Bulletin of Counseling and Psychotherapy, 2025)
Analog board and card games featuring reveal-and-react mechanics, characterized by immediate player responses to newly disclosed game elements, have emerged as promising tools for enhancing executive functions (EF), attention, memory, and problem-solving skills in children. This systematic review synthesizes findings from 13 studies, assessing the cognitive impact of reveal-and-react gameplay in participants aged 3–18, with particular emphasis on children aged ≤12 years. Results consistently indicate improvements across core EF domains such as inhibitory control, cognitive flexibility, and working memory. Notable games identified include Ghost Blitz, Dobble, Bee Alert, and Speed Cups, which provide structured yet engaging environments for cognitive training. The review underscores reveal-and-react mechanics as potent catalysts for developing rapid decision-making, attention control, and working memory updating. Moreover, these games hold significant educational and clinical potential, offering scalable, cost-effective interventions adaptable across diverse settings, including classrooms and therapeutic contexts. Despite limitations in study heterogeneity and longitudinal data scarcity, the collective evidence supports integrating these games into child-focused cognitive enhancement programs.